2019
DOI: 10.1088/1361-648x/ab5c2b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced magnetic and room temperature intrinsic magnetodielectric effect in Mn modified Ba2Mg2Fe12O22 Y-type hexaferrite

Abstract: We have reported a systematic investigation on structural, magnetic, magnetodielectric and magnetoimpedance characteristics of Y-type Ba 2 Mg 2 (Fe 1−x Mn x ) 12 O 22 (0 ⩽ x ⩽ 0.12) hexaferrite synthesized by solid-state reaction route. Rietveld refinement of x-ray diffraction pattern confirms the phase purity of all the samples with rhombohedral crystal structure. The Mn dopant modulates not only superexchange angle near to the boundary of magnetic blocks but also magnetic transition temperature. Temperature-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The classical ceramic technology is the most popular method for preparation of complex polycrystalline oxides. A large amount of research effort has been focused on the preparation of single-phase Y-type hexaferrites. In summary, the technique is based on a solid-state reaction of alkaline earth carbonates with metal oxides. The powders are homogenized by ball-milling and, after palletization, are synthesized at a high temperature in the 1100–1200 °C range to obtain single-phase Y-type hexaferrite.…”
Section: Synthesis Techniques Of Y-type Hexaferritesmentioning
confidence: 99%
See 2 more Smart Citations
“…The classical ceramic technology is the most popular method for preparation of complex polycrystalline oxides. A large amount of research effort has been focused on the preparation of single-phase Y-type hexaferrites. In summary, the technique is based on a solid-state reaction of alkaline earth carbonates with metal oxides. The powders are homogenized by ball-milling and, after palletization, are synthesized at a high temperature in the 1100–1200 °C range to obtain single-phase Y-type hexaferrite.…”
Section: Synthesis Techniques Of Y-type Hexaferritesmentioning
confidence: 99%
“…Abdullah et al investigated the Sr substitution effect in the Ba 2– x Sr x Mg 2 Fe 11.48 Mn 0.52 O 22 (0 < x ≤ 1) hexaferrite and found that the Sr substitution raises the spin ordering transition temperature from a proper screw state to a longitudinal conical spin state from 52 to 73 K and from a ferrimagnetic state to a proper screw state, from 210 to 315 K in a 100 Oe magnetic field. In another study, they found that Mn doping at Fe sites raises the transformation temperature from a ferrimagnetic state to a proper screw state from 190 to 208 K, while a drop was seen in the proper screw to longitudinal conical spin transformation temperature from 35 to 25 K in Ba 2 Mg 2 (Fe 1–x Mn x ) 12 O 22 in a magnetic field of 100 Oe.…”
Section: Magnetic Phase Transitionsmentioning
confidence: 99%
See 1 more Smart Citation